2005
DOI: 10.1016/j.trstmh.2004.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute vivax malaria with tafenoquine

Abstract: Tafenoquine is an 8-aminoquiniline related to primaquine with pre-clinical activity against a range of malaria species. We treated two acute cases of vivax malaria with tafenoquine (800 mg over three days) alone, instead of conventional chloroquine (1500 mg over three days) and primaquine (420 mg over 14 days). In addition to the convenience of this regimen, the rapid parasite clearances observed, coupled with a good clinical response and lack of recrudescence or relapse, indicate that further investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(38 citation statements)
references
References 7 publications
0
37
0
1
Order By: Relevance
“…Such an investigation is likely to yield a sobering sight about the blood schizontocidal potency of chloroquine in the study area since the response to chloroquine is apparently within the range of resistance. A future way of addressing the problem of chloroquine-resistant P. vivax could also consist of administering tafenoquine since this 5-phenoxy-primaquine has also blood schizontocidal impact beyond its anti-hypnozoitocidal activity [13] With mefl oquine and artemisinin, the parameters of the local response of P. vivax are also refl ecting resistance as to be expected with the free availability of artemisinin derivatives in the local market of Myanmar, and operational deployment of mefl oquine in the same country. In Th ailand, both mefl oquine and artesunate can only be used by the National Health Services for the treatment of confi rmed P. falciparum cases and even there, the synergistic interaction between both compounds is insuffi cient to prevent recrudescences [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an investigation is likely to yield a sobering sight about the blood schizontocidal potency of chloroquine in the study area since the response to chloroquine is apparently within the range of resistance. A future way of addressing the problem of chloroquine-resistant P. vivax could also consist of administering tafenoquine since this 5-phenoxy-primaquine has also blood schizontocidal impact beyond its anti-hypnozoitocidal activity [13] With mefl oquine and artemisinin, the parameters of the local response of P. vivax are also refl ecting resistance as to be expected with the free availability of artemisinin derivatives in the local market of Myanmar, and operational deployment of mefl oquine in the same country. In Th ailand, both mefl oquine and artesunate can only be used by the National Health Services for the treatment of confi rmed P. falciparum cases and even there, the synergistic interaction between both compounds is insuffi cient to prevent recrudescences [37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the long dose regimen of 14 days requires a high degree of compliance from the patient. It is expected that the introduction of a 5-phenoxyprimaquine, tafenoquine, will simplify the treatment, the more so as it has also activity against blood stages [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, quinoline derivatives have been interested of research for many years as a large number of natural products contain quinoline skeleton [16]. The quinoline and its derivatives are endowed with various activities, such as antimalarial [17], anticancer [18], anti-obesity [19], antihypertensive [20], HMG CoA (3-hydroxy-3-methyl glutaryl coenzyme) reductase, and phosphodiesterase 10A (PDE10A) inhibiting agents [21,22]. Consequently, the quinoline skeleton is often being chosen for the design of new bioactive molecules by a large number of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Quinoline derivatives exhibit various types of biological effects, including antibacterial, [1][2][3][4] tuberculostatic, [5][6][7] antimalarial, 8 and antitumor activity. 9,10 It was also found that quinoline derivatives containing phosphonate or phosphine oxide fragments 11,12 possess antiinflammatory 13 and antiHIV activity.…”
mentioning
confidence: 99%